2005
DOI: 10.1097/01.shk.0000170353.80318.d5
|View full text |Cite
|
Sign up to set email alerts
|

Harmful and Protective Roles of Neutrophils in Sepsis

Abstract: The current studies demonstrate protective and harmful effects of neutrophils (PMN) during experimental sepsis after cecal ligation and puncture (CLP). It is known that CLP induces signaling defects in blood PMN. When PMN were depleted 12 h after CLP, there were dramatic reductions in levels of bacteremia, evidence for reduced liver and renal dysfunction, sharp reductions in serum levels of cytokines (IL-1beta, IL-6, IL-10, TNF-alpha, and IL-2), and improved survival. In contrast, PMN depletion before CLP resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 42 publications
4
89
2
3
Order By: Relevance
“…from neutrophils and the subsequent degradation of ECM are believed to be key factors contributing to multiple organ failure (46). Elegant studies conducted by Bosio et al (47), further support the notion that neutrophils play a key pathogenic role in mediating host susceptibility to F. tularensis LVS insofar as B cell-deficient mice succumb to infection more readily than their wild-type counterparts.…”
Section: Discussionmentioning
confidence: 64%
“…from neutrophils and the subsequent degradation of ECM are believed to be key factors contributing to multiple organ failure (46). Elegant studies conducted by Bosio et al (47), further support the notion that neutrophils play a key pathogenic role in mediating host susceptibility to F. tularensis LVS insofar as B cell-deficient mice succumb to infection more readily than their wild-type counterparts.…”
Section: Discussionmentioning
confidence: 64%
“…It has been already shown that plasma red-ox status correlates to severity scores in critically ill patients in intensive care unit [21][22][23]. Several researchers have also reported that ROS increases in severe sepsis both in patients and animal models, compared with non-critical sepsis or controls, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, even though C57BL/6-Kit W-sh/W-sh mice had significantly more neutrophils in the blood, bone marrow and spleen at baseline than did the corresponding wild-type mice (Supplemental Figure 2), when tested 18 to 24 hours after the induction of moderately severe or severe CLP, the levels of intraperitoneal neutrophils or TNF were quite similar in C57BL/6-Kit It has been proposed that neutrophils can express opposing roles during CLP and other innate immune response to bacterial infection, promoting bacterial clearance but, in severe infections, also contributing to organ damage. 37 However, C57BL/6-Kit W-sh/W-sh mice engrafted with wild-type versus TNF-deficient mast cells may not differ only in the levels of TNF ( Figure 2C) and neutrophils ( Figure 2B) observed after severe CLP, but also in other mediators produced in this setting, which may be influenced by TNF and/or neutrophils. Proving which of these factors contribute most to lethality in this setting may be difficult.…”
Section: Discussionmentioning
confidence: 99%